2017
DOI: 10.4037/ajcc2017369
|View full text |Cite
|
Sign up to set email alerts
|

Cortrak-Assisted Feeding Tube Insertion: A Comprehensive Review of Adverse Events in the MAUDE Database

Abstract: Background Electromagnetic devices to guide feeding tube placement such as the CORTRAK Enteral Access System have shown promising results; however, researchers in recent studies have expressed concern that a higher level of user expertise may be required for safe use. Objectives To review adverse events related to CORTRAK-assisted feeding tube insertion reported in the Food and Drug Administration’s Manufacturer and User Faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 16 publications
0
22
1
3
Order By: Relevance
“…Os riscos envolvem três contextos de possíveis erros de posicionamento: colocação pulmonar -pneumotórax e pneumonias; colocação alta (esôfago) -broncoaspiração e pneumonias; e colocação baixa (pós-pilórica) -problemas de absorção intestinal e intolerância alimentar, além disso dificuldade no trajeto podem causar traumas e lesões perfurativas no trato gastrintestinal ou respiratório. Em qualquer destas situações a morte é um risco potencial 5,11,[16][17][18][19] .…”
Section: Revisão De Literaturaunclassified
“…Os riscos envolvem três contextos de possíveis erros de posicionamento: colocação pulmonar -pneumotórax e pneumonias; colocação alta (esôfago) -broncoaspiração e pneumonias; e colocação baixa (pós-pilórica) -problemas de absorção intestinal e intolerância alimentar, além disso dificuldade no trajeto podem causar traumas e lesões perfurativas no trato gastrintestinal ou respiratório. Em qualquer destas situações a morte é um risco potencial 5,11,[16][17][18][19] .…”
Section: Revisão De Literaturaunclassified
“…Recently some published articles have questioned the safety of the EMPD device and support continued use of abdominal radiographic verification . However, a retrospective review of the Food and Drug Administration's Manufacturer and User Facility Device Experience database found most misplacements to be from user error and misinterpretation by the clinician, not equipment related . This supports the need to further elucidate appropriate training and competency assessment when using an EMPD.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent complication is insertion of the FT into the pulmonary system, which can lead to pneumothorax, pneumonitis and death 2. CORTRAK Enteral Access System (EAS) is an electromagnetic device that has the benefit of providing real-time visualisation during the FT insertion.…”
Section: Introductionmentioning
confidence: 99%
“…CORTRAK Enteral Access System (EAS) is an electromagnetic device that has the benefit of providing real-time visualisation during the FT insertion. Research on CORTRAK-assisted FT insertion has shown positive outcomes through the use of specially trained superusers, which are most frequently registered nurses 2. Unfortunately, there is no evidence to suggest the ideal amount or type of training required by superusers.…”
Section: Introductionmentioning
confidence: 99%